A new species of Liolaemus (Squamata, Iguania, Liolaemini) endemic to the Auca Mahuida volcano, northwestern Patagonia, Argentina - Martinez, Lorena Elizabeth; Avila, Luciano Javier; Perez, Cristian Hernan Fulvio; Perez, Daniel Roberto; Sites, Jr., Jack W.; Morando, Mariana (Zootaxa, 2011)
We describe a new species of the Liolaemus bibronii complex. The new species differs from other members of the bibronii-alticolor group in color pattern, coloration and squamation. Liolaemus cyaneinotatus is endemic to the Auca Mahuida volcano in northwestern Patagonia.